Artefacts and Landscapes of Artificial Culture - Broncano, Fernando (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
À propos of the importance given by Ortega to the environment, in this work we understandthe environment from the anthropological notion of material culture as a horizon of possibilities created by artifacts. We first examine the functionalist notion of artifacts and extend it to an analogy between artifacts and concepts.